Shelf life extension of Peda using Caesalpinia sappan heartwood extract - PURI, RISHI KUMAR (Indian Journal of Dairy Science, 2018)
Present study was conducted to examine the feasibility of using heartwood extract of a medicinal plant Caesalpinia sappan, as potential preservative in peda; a khoa based sweet. The experiment comprised of analyses of changes in sensory, physico-chemical and microbiological properties taking place during storage at 4 and 30 Â°C. The samples were wrapped with parchment paper and packed in cardboard boxes with traditional white and brown (lal) peda samples as control. Treatment Peda was prepared by incorporating 0.09 per cent Caesalpinia sappan heartwood extract (w/v of milk) added during khoa preparation at 65 per cent TS. Treatment product possessed a significantly superior quality in terms of chemical (Thiobarbituric acid reactive substances-TBARS value, free fatty acid-FFA content and tyrosine value) and microbiological characteristics (Standard plate count-SPC, Yeast and mould and Coliform count). Shelf life of prepared product was recorded as 49 and 35 days, which was 21 and 14 days higher than that of control samples when stored at 4 and 30Â°C respectively. During storage, treatment peda exhibited superior sensory, chemical and microbiological quality in terms of FFA content, TBARS value, tyrosine value and SPC.